2017
DOI: 10.1016/j.ultrasmedbio.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Assessment of Human Meniscus

Abstract: The aim of the present study was to evaluate the applicability of ultrasound imaging to quantitative assessment of human meniscus in vitro. Meniscus samples (n = 26) were harvested from 13 knee joints of non-arthritic human cadavers. Subsequently, three locations (anterior, center and posterior) from each meniscus were imaged with two ultrasound transducers (frequencies 9 and 40 MHz), and quantitative ultrasound parameters were determined. Furthermore, partial-least-squares regression analysis was applied for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…We demonstrated the capability of optical spectroscopy in the NIR spectral range to estimate the biomechanical properties of the human meniscus. When compared with a high-frequency intra-articular ultrasound technique (E eq R 2 ¼ 0.49, RMSECV ¼ 0.08), 50 our results suggest that NIR spectroscopy (E eq R 2 ¼ 0.88, RMSECV ¼ 0.05) is a more viable candidate for nondestructive assessment of meniscus biomechanical properties, outperforming the acoustic technique in terms of accuracy and error.…”
Section: Discussionmentioning
confidence: 81%
“…We demonstrated the capability of optical spectroscopy in the NIR spectral range to estimate the biomechanical properties of the human meniscus. When compared with a high-frequency intra-articular ultrasound technique (E eq R 2 ¼ 0.49, RMSECV ¼ 0.08), 50 our results suggest that NIR spectroscopy (E eq R 2 ¼ 0.88, RMSECV ¼ 0.05) is a more viable candidate for nondestructive assessment of meniscus biomechanical properties, outperforming the acoustic technique in terms of accuracy and error.…”
Section: Discussionmentioning
confidence: 81%
“…During full-text review, study citations were examined, and 20 articles were identified and included. A total of 186 papers 29–31,33–215 were included for data extraction.…”
Section: Resultsmentioning
confidence: 99%
“…However, DLMs are considerably more likely to be unstable and result in tearing, pain and mechanical symptoms (popping, locking, snapping or giving way of the knee) (Hart et al 2008), especially in older children (Kocher et al 2003). The mechanical function of the meniscus may deteriorate if DLMs remain unaddressed (Viren et al 2017;Ha et al 2020), thus rendering DLMs more vulnerable to injury than normal menisci. Early screening is helpful in preventing injury among patients with DLMs, and surgery prior to any serious injury is likely to be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…Further, US provides real-time and dynamic assessment of neuromuscular diseases (Chang et al 2020;Wu et al 2021). With dramatic improvements in image quality, US has been reported to provide images of the meniscus that may offer results similar to those of MRI (Najafi et al 2006;Viren et al 2017), especially in detecting a meniscal tear (Najafi et al 2006;Shetty et al 2008). To our knowledge, most previous studies have been undertaken using linear array probes (LAPs), and accuracy remains controversial.…”
Section: Introductionmentioning
confidence: 99%